2010
DOI: 10.3389/fnbeh.2010.00179
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Long-Term Alcohol-Related Memory Reconsolidation: Role of β-Adrenoceptors and NMDA Receptors

Abstract: Disrupting reconsolidation of drug-related memories may be effective in reducing the incidence of relapse. In the current study we examine whether alcohol-related memories are prone to disruption by the β-adrenergic receptor antagonist propranolol (10 mg/kg) and the NMDA receptor antagonist MK801 (0.1 mg/kg) following their reactivation. In operant chambers, male Wistar rats were trained to self-administer a 12% alcohol solution. After 3 weeks of abstinence, the animals were placed in the self-administration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 48 publications
(83 reference statements)
1
60
1
Order By: Relevance
“…In this model, rodents are trained to lever press or nose poke for rewards, such as food, intravenous drug infusion, or intracranial stimulation (eg, of the lateral hypothalamus). Experiments have revealed that systemic propranolol injections administered after memory retrieval disrupt context-or cue-driven sucrose seeking (Diergaarde et al, 2006;Milton et al, 2008b), cocaine seeking (Milton et al, 2008b), and ethanol seeking (Wouda et al, 2010) within the SA paradigm (but see Milton and Everitt, 2010;Williams and Harding, 2014). However, these convincing experiments have been overshadowed by studies revealing no effect of propranolol when administered before memory retrieval (Lee and Everitt, 2008;Milton and Everitt, 2010).…”
Section: Rodent Sa Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, rodents are trained to lever press or nose poke for rewards, such as food, intravenous drug infusion, or intracranial stimulation (eg, of the lateral hypothalamus). Experiments have revealed that systemic propranolol injections administered after memory retrieval disrupt context-or cue-driven sucrose seeking (Diergaarde et al, 2006;Milton et al, 2008b), cocaine seeking (Milton et al, 2008b), and ethanol seeking (Wouda et al, 2010) within the SA paradigm (but see Milton and Everitt, 2010;Williams and Harding, 2014). However, these convincing experiments have been overshadowed by studies revealing no effect of propranolol when administered before memory retrieval (Lee and Everitt, 2008;Milton and Everitt, 2010).…”
Section: Rodent Sa Studiesmentioning
confidence: 99%
“…Synaptic plasticity is a critical mechanism for reconsolidation (Clem and Huganir, 2010). Moreover, NMDA receptor Impaired Sucrose (CR) Milton et al (2008b) Impaired Cocaine (CR) Milton et al (2008b) No effect Cocaine (reinstatement) Milton and Everitt (2010) Impaired EtOH (extinction) Wouda et al (2010) No effect EtOH (extinction) Williams and Harding (2014) Before No effect Sucrose (PCA) Lee and Everitt (2008) No effect Sucrose (PIT) Lee and Everitt (2008) No effect EtOH (PCA) Milton et al (2012) No effect EtOH (PIT) Milton et al (2012) Abbreviations: CR, conditioned reinforcement; PCA, Pavlovian conditioned approach; PIT, Pavlovian-to-instrumental transfer. Summary of findings for research examining the effectiveness of propranolol for reconsolidation blockade within the SA paradigm.…”
Section: Cellular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short CPP tests were chosen to induce reconsolidation while limiting CPP extinction across the initial tests. This length of test is standard for testing reconsolidation of drugassociated memories, and previous investigations using this length of CPP test have revealed a role for dHipp or b-AR signaling in reconsolidation of CPP memories (eg, Bernardi et al, 2009 andOtis et al, 2013) and self-administration memories (eg, Ramirez et al, 2009;Wells et al, 2011 andWouda et al, 2010). A CPP was determined when rats spent significantly more time within the previously cocainepaired chamber than in the saline-paired chamber.…”
Section: Conditioning and Testingmentioning
confidence: 99%
“…This has been demonstrated in a number of experimental paradigms using natural (Diergaarde et al 2006;Lee and Everitt 2008a), alcohol (Wouda et al 2010;Milton et al 2012), and addictive drug rewards (Lee et al 2005(Lee et al , 2006aMilton et al 2008a,b). However, there are two notable failures to observed memory reconsolidation in appetitive settings: instrumental responding (Hernandez and Kelley 2004) and Pavlovian goal-tracking (Blaiss and Janak 2007).…”
mentioning
confidence: 99%